Neural correlates of expert visuomotor performance in badminton players - Hülsdünker, T.; Strüder, H. K.; Mierau, A. (Medicine & Science in Sports & Exercise, 2016)
Introduction: Elite/skilled athletes participating in sports that require the initiation of targeted movements in response to visual cues under critical time pressure typically outperform nonathletes in a visuomotor reaction task. However, the exact physiological mechanisms of this advantage remain unclear. Therefore, this study aimed to determine the neurophysiological processes contributing to superior visuomotor performance in athletes using visual evoked potential (VEP).